PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK DISKALKULIA - Nuryani, Ani; Sowiyah, Sowiyah; Destini, Frida; Astuti, Nelly (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study was conducted to determine the effect of the discovery learning model assisted by flashcard media on the mathematics learning outcomes of students with dyscalculia. The data collection techniques included tests and non-tests. The research approach used a quasi-experimental design with a nonequivalent control group design. The population consisted of 103 students, with a sample of 51 students selected using purposive sampling. The results showed a significance value of <0.001<0.05, meaning H0 was rejected and Ha was accepted. This indicates that the use of the discovery learning model assisted by flashcard media has an effect on the mathematics learning outcomes of students with dyscalculia.